Characterization of true triaxial rock bursts in sandstones with different water contents - Chen, Kezhu; Zhou, Weijin; Pan, Yuangui; Zhuo, Ying; Zheng, Guoqiang (Frontiers in Earth Science, 2023)
The rockburst phenomenon occurs in dry red sandstone under high in situ stress, and the rockburst effect is weaker for a water-bearing rock. The rockburst effect on red sandstone with different water contents is analyzed in this paper. A true triaxial testing machine is used to conduct the loading, and acoustic emission recording equipment and a high-speed camera are used to monitor the acoustic signal inside the rock and the rock-caving situation throughout the entire process in order to analyze the characteristics of the acoustic emissions and the ejection form of the rockburst. The results show that rockburst occurs in dry red sandstone and 50% saturated red sandstone but not in saturated red sandstone. The phrase characteristics of the stress–strain curve of the dry rock vary more significantly than those of the water-bearing rock, and the elastic strain energy inside the rock decreases gradually as the water content increases. The double peak of the acoustic emissions curve occurs during the failure process of the dry rock and gradually transitions to a stepped pattern as the water content increases. The ejected fragments of dry red sandstone during the rockburst are abundant and large. The true triaxial test results illustrate the characteristic effect of the rockburst on red sandstone with different water contents, reveal the failure mode and ejection characteristics of red sandstone with different water contents, and demonstrate the influence of the water content on the rockburst characteristics of red sandstone. The results of this study provide a theoretical reference for the study of the rockburst mechanisms of similar hard rocks.